Hubungan tingkat pendidikan formal dengan parenting self-efficacy periode awal nifas pada ibu pasca sectio caesarea - Domas Chandra Pramudianti; Abkar Raden; Endang Koni Suryaningsih (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
Abstract: The research aimsto determine the relationship of the levelof formal education with parenting self-efficacy in the early period ofpostnatal maternal post Sectio Caesarea(SC).The methods is anobservational study with cross sectional design. The study populationincludes all mothers post SC in RSIA ‘Aisyiyah Klaten and DelangguPKU Muhammadiyah Hospital, the subject of the study involved 66people. Samples were selected purposively to the inclusion criteriaof exclusion. Data analysis using Spearman Rank at the 95% confidencelevel. The results is level of formal education have a meaningfulrelationship with parenting self-efficacy in the early postnatal periodwith a value of p = 0.000 (p 0.05).Keywords: formal education, parenting self-efficacy